A comparative analysis of agricultural research and extension reforms in China and India - Babu, Suresh Chandra; Huang, Jikun; Venkatesh, P.; Zhang, Yumei (Emerald Publishing Limited, 2015)
– There is growing interest from the global development community in the role of agricultural research and extension (AR & E) systems to achieve development targets. Despite this interest, many smallholders in developing countries continue to lack access to updated agricultural information and reliable services. In an effort to increase the effectiveness, impact, and reach of AR & E programs, many governments have attempted to reform their national systems. The paper aims to discuss these issues.– This paper systematically compares the systems and reforms of AR & E in China and India in order to draw out lessons applicable to developing countries. This paper first reviews the existing literature on AR & E systems and their role in agricultural and economic development. The authors then provide a detailed review and comparative analysis of the reforms and approaches implemented in the AR & E systems of China and India. The authors apply this comparative analysis to draw out lessons that can be applied to inform the reformation of AR & E systems in developing countries.– The authors find that although both countries face similar agricultural development challenges, each took a different approach in the reformation of AR & E to address these challenges. Each country’s approaches had different impacts on the effectiveness of the system. Lessons from the reformation of the AR & E systems in China and India can be used to inform and improve the impact of AR & E in developing countries.– The paper examines two systems together using a set of common indicators and factors. The paper’s value comes from its usefulness in informing future AR & E reforms in other developing countries in order to increase the impact of these reforms on development outcomes.